Modelling Of Torque And Speed Characterisation Of Double Stator Slotted Rotor Brushless DC Motor - Raja Othman, Raja Nor Firdaus Kashfi; Md Zuki, Nor Aishah; Che Ahmad, Suhairi Rizuan; Abdul Shukor, Fairul Azhar; Mat Isa, Siti Zulaika; Othman, Md Nazri (Institution Of Engineering And Technology (IET), 2018)
This study discusses the modelling of torque and speed characterisation of the double stator slotted rotor brushless DC motor (DSSR-BLDC). Most double stators have a surface mount rotor structure. The problem with this structure is that it has a large air gap, expensive permanent magnet, and cannot operate at high speed. In addition to flux leakage when this type of rotor structure is used. To overcome this problem, the DSSR-BLDC has been introduced. The usage of the DSSR-BLDC is to minimise the flux leakage, thus increasing the flux linkage. This will increase the torque production for the DSSR-BLDC. The aim of this research is to model the torque and speed characterisation of the DSSR-BLDC. This model uses the permeance analysis method and finite element method. The maximum torque and speed can be determined using both methods. The analyses of the electromagnetic torque, output power, and efficiency for various voltages are also presented. The simulation and measurement result show a good agreement with each other. The highest measurement value of the electromagnetic torque is 11 N m at 100 rpm. In conclusion, this study reveals that the modelling of the torque and speed characterisation of the DSSR-BLDC is suitable for portable applications.